An empirical investigation into the determinants of decision speed in product elimination decision processes. Issue 4 (August 2015) - Argouslidis, Paraskevas C.; Baltas, George; Mavrommatis, Alexis
Abstract This paper considers the determinants of decision speed in the area of product elimination, i.e. the decision of the firm to discontinue a product's manufacturing process. Because temporal efficiencies are beneficial to organizational action, scholars have sought to understand what determines decision speed. Non-routine decisions (e.g. mergers and acquisitions) have traditionally been the focus of decision speed research and calls for investigations with more routine decisions as units of analysis remain largely under-addressed. A more routine decision is product elimination. Whereas other product management decisions continuously attract research attention, product eliminations remain comparatively understudied, despite their importance, especially in today's global financial stringency. The knowledge gap is particularly evident in key organizational aspects of product elimination processes, like decision speed. Drawing on theories of the correlates of business strategy and organizational work, as well as on decision speed and product elimination research, this paper empirically tests a framework for main and moderating effects on product elimination decision reaching and implementation speed. Results from 175 consumer product elimination decisions show speed's dependence on (a) structural and temporal characteristics of decision making (i.e. locus of tactical responsibilities and decision authority in product elimination processes; polychronicity), (b) decision-specific factors (e.g. life stage of the product), and (c) environmental conditions (i.e. complexity; turbulence). The results enrich product elimination and decision speed research. Also, because consumer goods manufacturers eliminate products frequently, the results provide managerially useful insights into conjectures promoting or hindering temporal efficiencies in product elimination processes.